Asif Farrukhi’s Poems: Thematic and Compositional Study - Parveen, Rukhsana (sourcecoder, 2024)
Asif Farrukhi is a multi-dimensional creator. He has rendered valuable services in the field of fiction writing ,criticism and translation but few people in literary world are aware that he also contributed to poetry and published a collection of prose poems .He presented various topics in his own style by his poems. Asif Farrukhi expressed the contemporary situations through his prose poems. He also described the crisis of the country and social situation of Karachi. Asif Farrukhi was an erudite man. He was not only proficient in different languages but also has a deep familiarity with the literature of these languages, so he has used various signs and symbols in his poems. His services are the most valueable asset of literature.